THE RELATIONSHIP BETWEEN PREGNANT WOMEN'S KNOWLEDGE AND ATTITUDES TOWARDS COMPLIANCE IN CONSUMING FERROUS SULFATE (FE) TABLETS IN THE WORKING AREA OF PUSKESMAS SAMUDERA, THE REGENCY OF NORTH ACEH IN 2025 - Helmiana; US, Hafsah; Anita, Anita (Department of Midwifery, Health Polytechnic of Aceh, 2025)
Background: Anaemia during pregnancy, especially iron deficiency anemia, remains a serious public health problem in Indonesia. According to the 2021 Indonesian Basic Health Research (Riskesdas), the prevalence of anemia among pregnant women reached 48.9%. In Aceh Utara District, local health reports show that 42% of pregnant women were diagnosed with anemia in 2023. Although iron tablets (Fe) are routinely distributed by health centres, only around 65% of pregnant women adhere to the recommended regimen. Limited knowledge, negative attitudes, and concerns about side effects often drive this low compliance. This study aims to examine the relationship between pregnant women's knowledge and attitudes and their compliance with iron tablet use.Subjects and Method: This study employed a quantitative cross-sectional design. A total of 85 pregnant women who visit Puskesmas Samudera, The Regency, North Aceh, were selected using proportional random sampling. Data were collected using questionnaires and analyzed using the Chi-Square test to assess associations between variables.Results: Knowledge is related to the compliance of pregnant women in consuming Fe tablets with a p-value = 0.002 (p < 0.05), and the attitude of pregnant women is related to compliance in consuming Fe tablets, with a p-value of 0.012 (p < 0.05).Conclusion: Pregnant women's knowledge and attitudes towards iron tablets influence their compliance in consuming these tablets.